Do Business Groups Help or Hinder Technological Progress in Emerging Markets? Evidence from India - Sumon K. Bhaumik; Ying Zhou (Institute for the Study of Labor (IZA), 2014)
Business groups, which are ubiquitous in emerging market economies, balance the advantages of characteristics such as internal capital markets with the disadvantages such as inefficient internal distribution of resources and suppression of technological and other forms of innovativeness. In this paper, we examine, in the Indian context, whether business group affiliation provides an advantage over unaffiliated (or private independent) firms with respect to technological progress, which lies at the heart of wider economic growth and prosperity. Our results suggest that while business group affiliation did provide an advantage over private independent firms at the start of the sample period (2000), this advantage was more than offset by the turn of the century. We discuss the implications of our results for economic growth rates in emerging market economies.
Keywords: D24; L21; L22; O12; 330; business groups; technological progress; India